Does dynamic market competition with technological innovation leave no one behind? - Yongsheng Xu; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2019)
In this paper, we examine the performance of the market mechanism by focusing on whether no one, in the "long-run", can be left behind with technological innovation in the economy. We show that the market mechanism with technological innovation unavoidably leaves some individuals behind. We extend this negative result to a broader class of resource allocation mechanisms.
Keywords: D30; D51; D60; O33; P10; P20; P40; 330; dynamic market competition with technological innovation; Hicksian Optimism; the Walrasian allocation rule; Pareto efficiency; individual rationality